PELATIHAN PERCAKAPAN BAHASA INGGRIS TENTANG LIKE AND DISLIKE UNTUK ANAK-ANAK PANTI ASUHAN AR-RIDHO DEPOK JAWA BARAT - Delis Meta Tiana; Jimmi Jimmi; Cicih Nuraeni; Aprillia Aprillia (Bajang Institute, 2023)
Community service is the practical implementation of science, technology, art, and culture directly into society aimed at helping a particular community in various activities without expecting anything in return. In 2022, English Language and Literature study program lecturers held an English Conversation Workshop on Like and Dislike of children at Ar-Ridho Orphanage, Depok, West Java. The purpose of this workshop is to improve participants' English skills, especially speaking. Global competition is increasingly fierce demanding the creation of quality human resources, one of which is by having international communication skills, namely using English. A total of 20 participants attended this workshop face-to-face. The methods used are the lecture method and the role-play technique. With the implementation of this workshop, participants are expected to be able to enhance their confidence and motivation to speak and practice the material provided in daily conversations.